Patient experiences and discomfort associated with mid-palatal temporary skeletal anchorage devices - Aoife P. Barry; Vanessa Knode; Padhraig S. Fleming; Björn Ludwig (Progress in Orthodontics)
Abstract Background Mid-palatal placement of temporary skeletal anchorage devices (TSADs) has become increasingly popular among clinicians due to high success rates, low associated risk and streamlining and enhanced customization of associated supra-structures. There is however limited patient data in relation to associated experiences and impacts. Methods A survey of patients undergoing mid-palatal TSAD insertion was undertaken using a 27-item bespoke questionnaire. Questionnaires were sent using both electronic and surface mail with a 3-month period allowed for response. Pain experience; the use of analgesia; requirement for additional visits; impacts on hygiene, speech, eating, and hobbies; and social impacts were assessed. Reponses involved the use of a Visual Analogue Scale as well as binary information. Results Overall, 152 responses were obtained with 87.5% describing experience of TSAD insertion either “as expected” or “better”. Procedural pain was reported as mild in 62.5%. Local post-operative pain was scored as moderate in 21.1%. Some functional impairment was reported with 63.2% attributing difficulty with speech and 67.8% difficulty with eating due to the implant. However, these functional impairments were generally considered mild (by 68.1% and 60.2%, respectively) and most were very likely to recommend this treatment to others, with 65.1% (n = 99) scoring 8 or above out of 10. Conclusions Appreciable levels of pain, discomfort and functional impairment were noted with the use of mid-palatal TSADs. However, any unpleasant experiences were generally regarded as mild with most highly likely to recommend mid-palatal TSADs to prospective patients.